CALS-technologies in synthesis of multiassortmental manufacturing for phosphorus sludge utilization - Bessarabov, Arkadiy; Zakolodina, Tatyana; Sandu, Roman; Zaikov, Gennady (Publishing House of Lviv Polytechnic National University, 2009)
CALS-projects of sodium phosphite and hypophosphite technologies – products of phosphorus sludge utilization (one of the main wastes of phosphoric industry) were developed. CALS-technology of the flexible two-grocery production was developed based on the theory of the flexible scheme synthesis. Для утилізації фосфорногошламу (основного відпаду виробництва фосфатної кислоти) розроблений інформаційний проект гнучкої технології одержання фосфіту і гіпофосфіту натрію. Проект створений на основі інформаційних CALS-технологій.
Keywords: multiassortmental manufacturing; CALS technologies; phosphorus sludge; sodium phosphite; sodium hypophosphite; мультиасортиментне виробництво; CALS-технології; фосфорний шлам; фосфіт натрію; гіпофосфіт натрію